Allyl 4-Chlorophenyl Sulfone as a Versatile 1,1-Synthon for Sequential α-Alkylation/Cobalt-Catalyzed Allylic Substitution - Sekino, Tomoyuki; Sato, Shunta; Kuwabara, Kazuki; Takizawa, Koji; Yoshino, Tatsuhiko; Kojima, Masahiro; Matsunaga, Shigeki (Synthesis, 2020)
Despite their unique potential as rare 1,1-dipole synthons, allyl sulfones are rarely used in target-oriented syntheses, likely due to the lack of a general catalytic method for their branch-selective allylic substitution. Herein, we identified allyl 4-chlorophenyl sulfone as a versatile linchpin for both base-mediated α-derivatization and subsequent cobalt-catalyzed allylic substitution. The sequential transformations allow for highly regioselective access to branched allylic substitution products with a variety of aliphatic side chains. The photoredox-enabled cobalt catalysis is indispensable for achieving high yields and regioselectivity for the desulfonylative substitution in contrast to traditional metal-catalyzed protocols, which lead to inferior outcomes in the corresponding transformations.
Keywords: cobalt catalysis; photoredox catalysis; metallaphotoredox; allylation; sulfones; regioselectivity